How do you solve the system using the elimination method for -4x+y=-12 and 4x+2y=6?

1 Answer
Jul 4, 2015

Answer:

First add the two equations together to get #3y = -6#,
hence #y = -2#

Secondly, you can subtract twice the first equation from the second to get #12x = 30#, hence #x = 5/2#

Explanation:

Add the two equations together to get:

#-6 = -12 + 6 = (-4x+y) + (4x+2y) = 3y#

Divide both ends by #3# to get #y = -2#

Subtract twice the first equation from the second to get:

#30 = 6 - 2(-12) = (4x+2y) - 2(-4x+y) = 12x#

Divide both ends by #12# to get #x = 30/12 = 5/2#